A study of the traditional method of processing shea fruit into shea kernel: effect of some initial processing parameters on quality of the shea kernel - Antwi, Victor (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of the Degree of Master of Philosophy in Chemical Engineering,